Upacara Piodalan sebagai Media Pendidikan Sosial Religius-Ekonomi (Kajian Fenomenologi) - I Putu Agus Aryatnaya Giri; I Made Girinata; Kadek Agus Yoga Dwipranata (Sphatika: Jurnal Teologi, 2022)
The implementation of the piodalan ceremony at the temple is a symbol of maintaining the religiosity of Hindus as well as bonding the social relations of the Hindu community. Economic cycles in a series of piodalan ceremonies which are symbiotic mutualism also occur between Hindu communities, which in this case is very interesting to study. The results of the analysis show that the piodalan ceremony is a series of remembrance ceremonies to worship the manifestation of Ida Sang Hyang Widhi at a temple or certain places of worship whose implementation is carried out at a predetermined time (every six months or once a year). Religious social education in the piodalan ceremony is strongly felt starting from the process of making ceremonial facilities which are carried out in mutual cooperation, as well as in the ritual process. The piodalan ceremony is also a medium of economic education for Hindus. Some Hindus who are busy with the routines of the world of work who in reality do not have time to make ceremonial facilities will be helped by buying them from productive and active members of the community in the field of providing basic materials for religious ceremony infrastructure. In addition, the piodalan ceremony is a blessing for food and beverage traders around the temple because it is crowded with buyers. Direct economic education will occur because the Hindu community is trained to benefit and prosper one another.